Digitization issues in documenting cultural heritage with drones: Case study of Foinikas, Cyprus - Themistocleous, Kyriacos; Danezis, Chris (My University, 2018)
This paper will examine the use of traditional photogrammetry and LIDAR for documenting cultural heritage site. The case study area was Foinikas village, in the Limassol district of Cyprus, which dates back to the 11th century and has been abandoned from 1960, following the construction of the nearby Asprokremmos dam. Traditionally, photogrammetry has been used for documentation, by processing aerial images acquired from UAVs. However, with the recent development of new lightweight LiDAR scanners, it is now possible to mount professional grade LiDAR sensors on UAVs, which can be used to document areas with high accuracy. In this study, the abandoned village of Fionikas was documented using both photogrammetry using an RGB camera and a LiDAR scanner attached to a UAV. The results of the study found that both methods used provided high accuracy in the documentation of the site. The present paper is under the auspices of the ATHENA project, which receives funding from the European Union's Horizon 2020 research and innovation programme under grant agreement No 691936. Work programme H2020 under "Spreading Excellence and Widening Participation", call: H2020-TWINN-2015: Twinning (Coordination and Support Action).
Keywords: Cultural heritage; Documentation; LIDAR; Photogrammetry; UAV